(untitled) (Daffodil International University Journal of Science and Technology, 2010)
Spindle speed is an important parameter for the production of jute yarn [1]. An Apron Draft spinning frame was modified in to ring system by incorporating rings and travelers instead of flyers. The experiments were performed for investigating the effect of spindle speed on textile properties and productivity of jute yarn of 103 tex. The spindle speed was varied from 5000 rpm to 9000 rpm. The experiments were performed with Bangla White B (BWB) grade jute sliver of finisher drawing of linear density 2415 tex (70 lb/spy). The draft ratio and the twist used in the experiments were 23 and 240 tpm (turns per meter) respectively. The ring size was KW (4) 76 mm Ø. Steel travelers number 1, Type G, semicircular in shape were used in the experiment. Ten runs were performed for the experiment at the standard atmospheric condition, 20 ± 2°C, and relative humidity 65% ± 2%. The nominal count of the yarn produced was 103 tex. The yarns produced through the experiments were tested for different textile properties. Analysis of the test results shows that the spindle speed greatly influences the textile properties, such as strength, elongation, yarn breakage, productivity, quality ratio etc. of produced yarn. In consideration of the productivity, quality and other textile properties of the yarn, the optimum spindle speed was determined for the production of fine jute yarn of 103 tex. Key Words: Apron draft, spindle speed, fine jute yarn. DOI: 10.3329/diujst.v4i2.4358 Daffodil International University Journal of Science and Technology Vol.4(2) 2009 pp.1-5